MEDIA AUDIO VISUAL SEBAGAI SARANA PENGENALAN EKSPRESI EMOSI - Henie Kurniawati (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2012)
Media can be exploited for various purposes, and each media has its specificcharacteristics for specific purposes. The messages of emotional expression throughaudiovisual media can be one means to recognize the competencies of individuals inidentifying the emotional expression. The emotional expression is defined as a patternformed in the facial expression in relation to the types of emotion perceived. There are fourtypes of emotional expressions including feelings of anger, sadness, happiness, and scare.This research was aimed at developing instruments to recognize the emotional expressionsby using audio visual media.Subjects involved 32 graduate program students of Faculty of Psychology, Gadjah MadaUniversity, Yogyakarta. Data were collected by using rating scale to recognize the emotionalexpression(feelings of angry, sad, happy, and scary). Quantitative analysis were used in thisresearch with the result of assessment on raters’ responses as additional data. The results ofraters’ average assessment showed that the scenes 1 and 13 indicated the highest score forthe expression of angry feeling, the scenes 10 and 14 indicated the highest score for theexpression of sadness, scenes 11 and 15 the highest score for the expression of happiness,and scenes 8 and 12 the highest score for the expression of scare. The fragments of thescenes were able to be exploited as instruments successfully passed the selection to recognizethe emotional expression.